Thyroid hormone receptors are required for the melatonin‐dependent control of Rfrp gene expression in mice. Issue 9 (10th August 2020) - Quignon, Clarisse; Beymer, Matthew; Gauthier, Karine; Gauer, François; Simonneaux, Valérie
Abstract: Mammals adapt to seasons using a neuroendocrine calendar defined by the photoperiodic change in the nighttime melatonin production. Under short photoperiod, melatonin inhibits the pars tuberalis production of TSHβ, which, in turn, acts on tanycytes to regulate the deiodinase 2/3 balance resulting in a finely tuned seasonal control of the intra‐hypothalamic thyroid hormone T3. Despite the pivotal role of this T3 signaling for synchronizing reproduction with the seasons, T3 cellular targets remain unknown. One candidate is a population of hypothalamic neurons expressing Rfrp, the gene encoding the RFRP‐3 peptide, thought to be integral for modulating rodent's seasonal reproduction. Here we show that nighttime melatonin supplementation in the drinking water of melatonin‐deficient C57BL/6J mice mimics photoperiodic variations in the expression of the genes Tshb, Dio2, Dio3, and Rfrp, as observed in melatonin‐proficient mammals. Notably, we report that this melatonin regulation of Rfrp expression is no longer observed in mice carrying a global mutation of the T3 receptor, TRα, but is conserved in mice with a selective neuronal mutation of TRα. In line with this observation, we find that TRα is widely expressed in the tanycytes. Altogether, our data demonstrate that the melatonin‐driven T3 signal regulates RFRP‐3 neurons through non‐neuronal, possibly tanycytic, TRα.